Roles Of Leaders In Managing Change: A Case Study Of An Electrical & Electronic (E&E) MNC In Penang - Md Kamil, Mohamed Yusoff (2014)
This paper aims to examine the roles of leaders in managing change in an electrical and electronic (E&E) manufacturing organization in National Instrument Penang and explores the influences on the three stages of managing change (unfreeze, moving & refreeze) as suggested by Kurk Lewin in his theory Change Management Theory including the barriers and the lessons learned as when change is required. Qualitative methodology was utilized involved in-depth interviewing with eight respondents. Three subgroups constituted the sample including director, department/area heads and employees. An interview protocol was developed with content analysis using themes and SWOT was performed. Finding reveals that leaders playa significant roles in managing change. Study also found that barriers exist from various perspectives. The lessons learned are also shared based on the experience of the leaders in managing change. Understanding the roles of leaders in managing change including the barriers will help organization leaders to consider practices and policies that facilitate change. Through the lessons learned, leaders will be able to enhance their changes processes and avoid past mistakes. To sum up, organizations need leaders to manage and facilitate changes.